The Role of the Dispute Settlement Body (DSB) in the Settlement of Trade Disputes Between Member Countries of the World Trade Organization (WTO) - Eddy (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2023)
The flow of globalization that is taking place more rapidly at this time makes free trade no longer unstoppable. The dominance of the WTO in regulating the international trade system cannot be separated from the rapid and dynamic economic growth and development among nations. In this development, disputes between countries in international trade will certainly occur. This research aims to examine the role of the Dispute Settlement Body (DSB) in the settlement of trade disputes between member countries of the World Trade Organization (WTO). This research uses a normative legal research method and data collection is done by literature study. The results of this study showed that the dispute resolution system through the Dispute Settlement Body of the WTO is set forth in the Understanding of Rules and Procedures Governing the Settlement of Disputes. The substance of the provisions contained in this section is the interpretation and implementation of the provisions of Article III of the GATT of 1947 and the implementing agency is the Dispute Settlement Body. The institution is part of the WTO General Council so all member countries are bound by its rules and regulations and have the same right to use the existence of the Dispute Settlement Body.